RAPID GROWTH OF DIAMONDITE AT THE CONTACT BETWEEN GRAPHITE AND CARBONATE MELT: EXPERIMENTS AT 7.5-8.5 GPA - Litvin Yu.A.; Spivak A.V. (My University, 2003)
Based on high PT experiments, the present work demonstrates the possibility of formation of monomineral diamondite-type polycrystalline intergrowths in modeling carbonate-carbon and carbonate-silicate-carbon melts at their contacts with graphite.